Three-Dimensional Speckle Tracking Echocardiography-Derived Left Atrial Strain Parameters Are Reduced in Patients with Atrial Fibrillation (Results from the MAGYAR-Path Study). - Chadaide, Számi; Domsik, Péter; Kalapos, Anita; Sághy, László; Forster, Tamás; Nemes, Attila (Echocardiography, 2013)
Objective: Three-dimensional (3D) speckle tracking echocardiography (3 DSTE) is a novel imaging modality for assessing cardiac function. We aimed to analyze left atrial ( LA) function using 3 DSTE in patients with atrial fibrillation ( AF). Methods: 3 DSTE was performed in 20 patients prior to their pulmonary vein isolation for AF. Every patient underwent a complete two-dimensional echocardiographic study at the same time. 3 DSTE-derived circumferential ( CS), longitudinal ( LS), radial ( RS), 3D (3 DS), and area strain ( AS) values were measured in the basal (b), mid (m), and superior (s) regions of the LA. 3 DSTE-defined maximal ( LAmax) and minimal LA volumes ( LAmin) and LA total emptying fraction were calculated automatically. Eleven randomly selected age- and gender-matched healthy volunteers served as controls. Results: Patients with AF had significantly larger LAmax and LAmin and reduced LS, RS and CS.3 DS and AS were significantly lower throughout the LA in cases with AF (3 DS−b, −m, −s [ AF patients vs. controls]: −18 ± 8% vs. −29 ± 8%, P = 0.001; −14 ± 6% vs. −22 ± 7%, P = 0.002; −10 ± 7% vs. −20 ± 9%, P = 0.002; AS−b, −m, −s [ AF patients vs. controls]: 35 ± 15% vs. 52 ± 13%, P = 0.004; 50 ± 21% vs. 72 ± 19%, P = 0.009; 31 ± 21% vs. 65 ± 27%, P < 0.0001, respectively). Conclusions: 3 DSTE-derived 'uni-dimensional' LS, RS, CS, as well as novel strain parameters (3 DS, AS) are significantly reduced in patients with AF compared to matched controls. 3 DS and AS might be new strain parameters providing further insights into the alterations of LA function in patients developing AF.